The Theology of the Book of Revelation - Bauckham, Richard (New York Cambridge University Press, 1993)
Publisher description: Richard Bauckham expounds the theology of the Book of Revelation: its understanding of God, Christ and the Spirit, the role of the Church in the world, and the hope of the coming of God's universal kingdom. Close attention is paid b
Keywords: Bible. -- Revelation -- Theology. Bible. -- Revelation. Bible. -- New Testament. -- Apocalypse -- Théologie. 11.46 study and interpretation of the New Testament. Theology. Bibel -- Offenbarung des Johannes Theologie Openbaring van Johannes (bijbelboek) T